Public Attitudes and Willingness to Pay for Cultured Meat: A Cross-Sectional Experimental Study - Kantor, Bella Nichole; Kantor, Jonathan (Frontiers in Sustainable Food Systems, 2021)
Previous research has suggested that the general public is divided over their willingness to consider consuming cultured meat (CM) products. As commercial backing for cultured meat startups increases and the public interest in the US, Europe, and developing countries expands, formally evaluating attitudes to these products will become increasingly important. Willingness to pay (WTP) may provide insight into the level of acceptability of CM products, highlight latent societal preferences, and suggest commercial opportunities. To date, no studies have evaluated the societal WTP for CM products. A cross-sectional internet-based survey was distributed to 300 respondents in the US general population using a survey panel design. The mean age was 30 (range: 18-76), and 47% of respondents were male. We presented respondents with a series of scenarios relating to CM products, framing CM burgers as environmentally friendly versus as a better alternative to traditional burgers. Prior research has highlighted taste and price as areas of societal concern, but no studies have rigorously evaluated the intersection between these considerations. When CM products were framed as being equivalent in taste to conventional meat, and where their environmental benefits were stressed, respondents were willing to pay significantly more than for a traditional burger (2.11 versus 1.00). This WTP jumped to 2.66 when framing the CM burger as the best burger, reflecting a 266% premium that consumers were willing to pay for an appropriately framed CM burger. Framing CM burgers as a better alternative to traditional burgers, rather than focusing on their environmental impact, similarly led to the highest desirability ratings. These preferences were also reflected in a contingent valuation discrete choice experiment examining preferences for paying 1 for a traditional burger versus 2 for a CM burger. These findings support our hypothesis regarding the existence of what we term the gold-standard bias, a cognitive bias that systematically favors a product or service framed as the best available choice over and above its marginal benefit, and has significant and broad implications for feasibility, pricing, and marketing, suggesting the need for further research in this area.